Material properties and operating configurations of membrane reactors for propane dehydrogenation. Issue 3 (11th December 2014) - Choi, Seung‐Won; Jones, Christopher W.; Nair, Sankar; Sholl, David S.; Moore, Jason S.; Liu, Yujun; Dixit, Ravindra S.; Pendergast, John G.
<x xml:space="preserve">Abstract</x> A modeling‐based approach is presented to understand physically realistic and technologically interesting material properties and operating configurations of packed‐bed membrane reactors (PBMRs) for propane dehydrogenation (PDH). PBMRs composed of microporous or mesoporous membranes combined with a PDH catalyst are considered. The influence of reaction and membrane transport parameters, as well as operating parameters such as sweep flow and catalyst placement, are investigated to determine desired "operating windows" for isothermal and nonisothermal operation. Higher Damköhler (Da) and lower Péclet (Pe) numbers are generally helpful, but are much more beneficial with highly H2‐selective membranes rather than higher‐flux, lower‐selectivity membranes. H2‐selective membranes show a plateau region of conversion that can be overcome by a large sweep flow or countercurrent operation. The latter shows a complex trade‐off between kinetics and permeation, and is effective only in a limited window. H2‐selective PBMRs will greatly benefit from the fabrication of thin (∼1 µm or less) membranes. © 2014 American Institute of Chemical Engineers AIChE J, 61: 922–935, 2015